Is theatre utilization a valid performance indicator for NHS operating theatres? - Rennie John; Papagrigoriadis Savvas; Mcguire Alistair; Tekkis Paris; Faiz Omar; Leather Andrew (BMC, 2008)
Abstract Background Utilization is used as the principal marker of theatre performance in the NHS. This study investigated its validity as: a managerial tool, an inter-Trust indicator of efficient theatre use and as a marker of service performance for surgeons. Methods A multivariate linear regression model was constructed using theatre data comprising all elective general surgical operating lists performed at a NHS Teaching hospital over a seven-year period. The model investigated the influence of: operating list size, individual surgeons and anaesthetists, late-starts, overruns, session type and theatre suite on utilization (%). Results 7,283 inpatient and 8,314 day case operations were performed on 3,234 and 2,092 lists respectively. Multivariate analysis demonstrated that the strongest independent predictors of list utilization were the size of the operating list (p < 0.01) and whether the list overran (p < 0.01). Surgeons differed in their ability to influence utilization. Their overall influence upon utilization was however small. Conclusion Theatre utilization broadly reflects the surgical volume successfully admitted and operated on elective lists. At extreme values it can expose administrative process failure within individual Trusts but probably lacks specificity for meaningful use as an inter-Trust theatre performance indicator. Unadjusted utilization rates fail to reflect the service performance of surgeons, as their ability to influence it is small.